β-diketone accumulation in response to drought stress is weakened in modern bread wheat varieties (Triticum aestivum L.) - Kuruparan, Aswini; Gao, Peng; Soolanayakanahally, Raju; Kumar, Santosh; Gonzales-Vigil, Eliana (Frontiers in Plant Science, 2024)
Cuticular waxes coating leaf surfaces can help tolerate drought events by reducing non-stomatal water loss. Despite their role in drought tolerance, little is known about how cuticular wax composition has changed during breeding in Canadian bread wheat (Triticum aestivum L.) varieties. To fill in this gap, flag leaves of the Canadian Heritage Bread Wheat Panel, which includes 30 varieties released between 1842 and 2018, were surveyed to determine if and how cuticular wax composition in wheat has changed at two breeding ecozones over this period. Following this, a subset of varieties was subjected to drought conditions to compare their responses. As expected, modern varieties outperformed old varieties with a significantly larger head length and reaching maturity earlier. Yet, when challenged with drought, old varieties were able to significantly increase the accumulation of β-diketones to a higher extent than modern varieties. Furthermore, RNAseq was performed on the flag leaf of four modern varieties to identify potential markers that could be used for selection of higher accumulation of cuticular waxes. This analysis revealed that the W1 locus is a good candidate for selecting higher accumulation of β-diketones. These findings indicate that the variation in cuticular waxes upon drought could be further incorporated in breeding of future bread wheat varieties.